(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nurhalisa N, Nur I, Suryani S. 2022. Potential extracts of wedge sea hare (Dolabella auricularia) as immunostimulators in comet fish (Carassius auratus auratus) infected by Aeromonas hydrophila. Biodiversitas 23: 1884-1893. Microencapsulation is an innovative method to protect the active compound of pharmaceutical material from environmental impacts or unwanted conditions. This study aims to determine the active compound content and appropriate concentration of wedge sea hare extract (Dolabella auricularia) using the microencapsulation method to treat Aeromonas hydrophila bacterial which infected in comet fish (Carassius auratus auratus). The treatment consisted of three concentrations of D. auricularia extract (6.3, 7 and 7.7 g/kg feed) and commercial feed as a positive control in triplicates. C. a. auratus fed with experimental diets twice a day (8.00 a.m and 4.00 p.m) for 30 days of culture period before being challenged with an injection of A. hydrophila. Blood profile, weight gain, survival and relative survival of C. a. auratus were observed before and after the challenge test. The characteristics and types of active compounds in the extract were observed qualitatively, as well as the morphology and particle size distribution of the microcapsules. The results showed that D. auricularia extract contained phenol, tannins, steroids, terpenoids, alkaloids, and saponins. The microcapsules in all treatments were a spherical shape. The average diameter was similar to all extract treatments. The addition of D. auricularia extract microcapsules in the feed produced significantly different results on the blood profile, weight gain and survival. The highest of total leukocytes, total erythrocytes, hematocrit and blood hemoglobin were obtained in addition to 7.7 g D. auricularia extract/kg of feed with respective values ??of 7.35±0.94×104 cell.mm-3, 2.83±0.03×106 cell.mm-3, 22.43±0.03% and 6.72±0.02 g.dL-1, respectively. The highest weight gain was found in fish-fed diets contained of 7.7 g of D. auricularia extract (3.37 g). The highest relative survival and survival were found in the treatment of 7 and 7.7 g extract/kg of feed, which was 100%. This study concluded that microencapsulated with D. auricularia extract at dose 7 g extract/kg of feed was the optimum dose for C. a. auratus infected with A. hydrophila.